Relapsed Wilms’ tumor with pulmonary metastases – a case report - Kwolczak, Justyna; Roszkowska, Anna; Winiarz, Aleksandra; Świerszcz, Łukasz; Winiarz, Marek; Nurzyńska-Flak, Joanna; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Introduction: Wilms’ tumor is the most common malignant renal tumor in childhood. It accounts for about 95% of kidney tumors diagnosed in children. The delay in diagnosing neoplastic disease in children at an early stage is due to the occurrence of asymptomatic mass in abdomen as the only sign of the disease. Case report: We discuss a 5-year-old boy case, with Wilms’ tumor of the right kidney. Diagnosis was based on the results of imaging examinations; no fine needle aspiration biopsy was performed. The patient underwent nephrectomy and preoperative and postoperative chemotherapy. During the follow-up period, 11 months after the end of treatment, the patient developed respiratory symptoms. Histopathological examination confirmed tumor metastases of Wilms in the lungs. Discussion: Oncological vigilance comprises challenge for contemporary medicine. It is necessary to take into account the oncological status of the patient regardless the time of the last check-up in the oncological clinic, especially due to the fact that childhood cancers are characterized by dynamic growth.